Anti-diarrhoeal Effects of Aqueous Extract of Vitex doniana Stem Bark in Castor Oil-induced Wistar Rats - Amuzat, Aliyu O.; Ndatsu, Yakubu; Adisa, Mohammed J.; Sulaiman, Rukayyah S.; Mohammed, Hadiza; Yusuf, Abubakar A.; Ndayako, Hauwa M. (Tanzania Journal of Science, 2020)
Vitex doniana is a medicinal plant commonly used in traditional medicine for the treatment of diarrhoea-related disorders. In the present study, aqueous extract of Vitex doniana stem bark was evaluated for anti-diarrhoeal effects. Thirty albino rats of average weight 124 ± 4.35 g were distributed into five groups. Groups 1, 2, 3, 4 and 5 were orally administered 2 mL of normal saline, 2.5 mg/kg bodyweight (bw) loperamide, 100, 200, 400 mg/kg bodyweight of aqueous extract of V. doniana stem bark, respectively. The extract was evaluated using feacal characteristics, gastrointestinal motility and enteropooling test. Results for phytochemical screening revealed the presence of tannins, cardiac glycosides, phenols, steroids and saponins. Aqueous extract of Vitex doniana stem bark significantly (p < 0.05) reduced total stool frequency (TSF). 100 mg/kg bw of the extract had the least TSF (4.80 ± 1.64) when compared with the reference drug (5.75 ± 2.98). 100 mg/kg bw and 400 mg/kg bw showed higher percentage inhibition of defecation than the standard drug. The extract also exhibited inhibition of wet stooling and intestinal secretion. It possesses anti-diarrhoeal effects and thus could be a potential source of new drug for the treatment of diarrhoea.